Antimicrobial effect of fungal melanin in combination with plant oils for the treatment of wood - Tran-Ly, Anh N.; Heeb, Markus; Kalac, Tine; Schwarze, Francis W. M. R. (Frontiers in Materials, 2022)
Microbial deterioration of wood has gradually destroyed precious historic musical instruments. The serpentino (English: serpent/little snake), a wind instrument used for over 400 years and considered the godfather of modern instruments such as the saxophone and the tuba. Many original instruments have been totally destroyed due to colonization and degradation by bacteria and fungi. Reconstructing the serpent in particular and other ancient instruments in general requires the preservation of wood against bio-deterioration. Conventional chemical preservatives based on copper and boron compounds have been used in the wood processing industry; however, they are not ideal for protecting musical instruments and may pose negative impact on health and safety of musicians with direct mouth contact. Non-biocidal preservatives, such as plant oils, have attracted a lot of attention. Herein, we report the antimicrobial efficacy of plant oils, alone and in combination with fungal melanin, for protecting walnut wood that is used to make the serpent, against oral bacteria and wood-decay fungi. Linseed and tea tree oils were found to have a strong antibacterial effect, reducing the survival rate of Streptococcus mutans, a bacterium commonly found in human saliva, to below 1%. Impregnation of wood with plant oils and melanin was significantly in-creased the antibacterial effect when compared to that of the oil(s) alone. A satisfactory antifungal effect was also achieved after 2 weeks as indicated by a reduction (<10%) in the survival rate of Chaetomium globosum on the radial longitudinal wood surface. In addition, the treated wood samples absorbed less water than the untreated wood and maintained their dimensions at different humidity conditions, highlighting the potential of this approach for wood protection.